2021
DOI: 10.1002/tox.23370
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PSMA3‐AS1 promotes cell proliferation, migration, and invasion in ovarian cancer by activating the PI3K/Akt pathway via the miR‐378a‐3p/GALNT3 axis

Abstract: The crucial roles of the long noncoding RNAs (lncRNAs) in the development of ovarian cancer (OC) have been extensively studied. According to the prediction result from the Kaplan-Meier Plotter database, high expression of lncRNA proteasome subunit α type-3 antisense RNA1 (PSMA3-AS1) is associated with the poor prognosis in patients with OC. Thus, the study aimed to investigate the role of lncRNA PSMA3-AS1 in OC. Reverse transcription quantitative polymerase chain reaction analysis revealed that PSMA3-AS1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…In order to develop effective drugs for OC target treatment, the study of etiology and progression mechanism at the molecular level has become the hotspot. 24 In this study, the influence of REG3A resistance. 25 In this study, REG3A knockdown reduced the DDP resistance of both OC cells and DDP resistance OC cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In order to develop effective drugs for OC target treatment, the study of etiology and progression mechanism at the molecular level has become the hotspot. 24 In this study, the influence of REG3A resistance. 25 In this study, REG3A knockdown reduced the DDP resistance of both OC cells and DDP resistance OC cells.…”
Section: Discussionmentioning
confidence: 92%
“…However, the prognosis of OC patients remains unsatisfactory. In order to develop effective drugs for OC target treatment, the study of etiology and progression mechanism at the molecular level has become the hotspot 24 . In this study, the influence of REG3A on the progression of OC was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signaling pathway has been shown to play an important role in the occurrence and development of OC. [30][31][32] Therefore, CBD may affect the growth of OC cells through this pathway.…”
Section: Cbd Inhibits Ovarian Cancer Cells By Regulating the Pi3k/akt...mentioning
confidence: 99%
“…This was associated with enhanced migration and invasion, which was abrogated by the addition of an EGRF inhibitor or an Akt inhibitor. Xu et al (2021) reported that upon GALNT3 knockdown in ovarian cancer cells, levels of phosphorylated PI3K and phosphorylated Akt decreased, suggesting that GALNT3 activated the PI3K/Akt pathway. Moreover, they demonstrated that the microRNA miR-378a-3p suppressed the expression of PI3K and pAkt, which could be rescued by GALNT3.…”
Section: Galnts Alter Galnac O-glycosylation Of Signal Induction Rece...mentioning
confidence: 99%